2019
DOI: 10.4103/ija.ija_787_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immobilised cervical spine on oropharyngeal sealing pressure with Ambu AuraGain™ Supraglottic airway: A randomised crossover trial

Abstract: Background and Aims: Ambu ® AuraGain™ laryngeal airway (AuraGain) is one of the newer supraglottic airway device introduced in 2014. Cervical spine stabilisation with hard cervical collar makes insertion of supraglottic airways and tracheal intubation difficult. This study was conducted to investigate whether the presence of a cervical collar affects the oropharyngeal sealing pressure (OSP) and fibreoptic view of the glottis (Brimacombe score) in airways secured with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A wide range of supraglottic airway devices (SADs) have been assessed for their impact on cervical spine movement and their performance with cervical spine immobilisation in patients and cadavers. Most first‐ and second‐generation SADs studied perform either equally well or better when cervical spine immobilisation is in place, with little data showing the superiority of one device over another [24–27]. Cervical spine immobilisation, therefore, does not hamper SAD effectiveness in terms of ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of supraglottic airway devices (SADs) have been assessed for their impact on cervical spine movement and their performance with cervical spine immobilisation in patients and cadavers. Most first‐ and second‐generation SADs studied perform either equally well or better when cervical spine immobilisation is in place, with little data showing the superiority of one device over another [24–27]. Cervical spine immobilisation, therefore, does not hamper SAD effectiveness in terms of ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Mihara et al [8] on pediatric patients concluded that the i-Gel ® (Intersurgical Ltd., UK, second generation) was easier to place than the Ambu® AuraGain™ and therefore caused less oropharyngeal damage, but lower airway pressures were obtained with the Ambu® AuraGain. Likewise, Uthaman et al [9] found that use of the Ambu® AuraGain™ LMA in patients with an immobilized cervical spine had adequate oropharyngeal leak pressure with a stiff collar. Although studies on the thirdgeneration airway device, the Ambu® AuraGain™ LMA, are more limited, most studies performed with other LMA variants showed that the Ambu® AuraGain™ LMA is equivalent or superior to LMA [7,10,11].…”
Section: Discussionmentioning
confidence: 97%
“…[ 6 ] and Uthaman et al . [ 11 ] have reported the mean ± standard deviation (SD) of OSP with LMA BlockBuster ® and Ambu® AuraGain™ as 33.7 ± 1.8 cm H 2 O and 29.6 ± 3.7 cm H 2 O, respectively, in adult patients. Taking into account the difference in OSP between these two devices to be 4.1 cm H 2 O, we needed to study 17 participants in each of the study groups to be able to reject the null hypothesis that Ambu® AuraGain™ and LMA BlockBuster ® both provide equal seal pressures.…”
Section: Methodsmentioning
confidence: 99%